Application of an object-oriented programming paradigm in three-dimensional computer modeling of mechanically active gastrointestinal tissues. - Rashev, P.Z.
The aim of this study was to develop a novel three-dimensional (3-D) object oriented modeling approach incorporating knowledge of the anatomy, electrophysiology, and mechanics of externally stimulated excitable gastrointestinal (GI) tissues and emphasizing the "stimulus-response" principle of extracting the modeling parameters. The modeling method used clusters of class hierarchies representing GI tissues from three perspectives: 1) anatomical; 2) electrophysiological; and 3) mechanical. We elaborated on the first four phases of the object-oriented system development life-cycle: 1) analysis; 2) design; 3) implementation; and 4) testing. Generalized cylinders were used for the implementation of 3-D tissue objects modeling the cecum, the descending colon, and the colonic circular smooth muscle tissue. The model was tested using external neural electrical tissue excitation of the descending colon with virtual implanted electrodes and the stimulating current density distributions over the modeled surfaces were calculated. Finally, the tissue deformations invoked by electrical stimulation were estimated and represented by a mesh-surface visualization technique.
Keywords: 3D computer modeling; 3D tissue objects; Anatomy; Cecum; Colonic circular smooth muscle tissue; Descending colon; Electrophysiology; External neural electrical tissue excitation; Externally stimulated excitable gastrointestinal tissues; Gastrointestinal organs; Generalized cylinders; Mechanically active gastrointestinal tissues; Mesh-surface visualization technique; Microprocessor control; Neural electrical stimulation; Object-oriented programming; Stimulus-response.; Tissue deformations; Virtual implanted electrodes